EVALUATION OF APICAL ROOT RESORPTION IN ENDODONTICALLY TREATED AND VITAL TEETH IN ADULT ORTHODONTIC SUBJECTS - Khan, Abdul Rahman; Fida, Mubassar; Shaikh, Attiya (Journal of Ayub Medical College Abbottabad, 2018)
Background: External apical root resorption (EARR) is one of the detrimental outcomes of an orthodontic treatment. The study was aimed to compare the mean EARR between endodontically treated and its contralateral vital tooth in adult orthodontic subjects. Methods: A total of 30 subjects were included in the study. EARR was evaluated on pretreatment and post-treatment orthopantomograms using Rogan Delft View Pro-X software. Equal number of endodontically treated and their contralateral vital teeth were evaluated. Linge and Linge method was used to evaluate the pretreatment and post-treatment root lengths. For comparison of EARR between genders, treatment type and vital versus endodontically treated teeth, Mann-Whitney U Test was applied. Spearman correlation was applied to determine the correlation of EARR with age of the patient, duration of treatment and pretreatment root length. A probability value of ‰¤0.05 was kept as statistically significant. Results: Vital teeth showed more root resorption as compared to endodontically treated teeth and in females as compared to males. A weak positive correlation was found between the root resorption and patient’s age & pretreatment root length. In vital teeth, a weak negative correlation was appeared between root resorption and duration of the treatment. However, none of these correlations were significant. Conclusions: EARR appeared to be greater in vital as compared to the root filled teeth and in females as compared to the males. However, EARR was not significantly correlated with duration of treatment, age of patient and pretreatment root length. Keywords: Orthodontic Treatment, Root Resorption, Root Apex, Endodontically Treated, Vital Teeth